2009
DOI: 10.1111/j.1526-100x.2008.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Rewetting of Cutaway Peatlands: Are We Re‐Creating Hot Spots of Methane Emissions?

Abstract: Hot spots of CH 4 emissions are a typical feature of pristine peatlands at the microsite and landscape scale. To determine whether rewetting and lake construction in a cutaway peatland would result in the re-creation of hot spots, we first measured CH 4 fluxes over a 2-year period with static chambers and estimated annual emissions. Second, to assess whether rewetting and lake creation would produce hot spots at the landscape level, we hypothesized a number of alternative land use scenarios for the peatland fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
78
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 41 publications
(49 reference statements)
10
78
0
Order By: Relevance
“…by raising the local groundwater table, is currently being implemented in Germany with the explicit goal of reducing GHG emissions (Höper et al, 2008). Rewetting principally reduces CO 2 emissions but can often lead to a sharp increase in CH 4 release, as confirmed by field studies in fen (Hendriks et al, 2007;Wilson et al, 2008) and bog ecosystems (Tuittila et al, 2000;Drösler, 2005).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…by raising the local groundwater table, is currently being implemented in Germany with the explicit goal of reducing GHG emissions (Höper et al, 2008). Rewetting principally reduces CO 2 emissions but can often lead to a sharp increase in CH 4 release, as confirmed by field studies in fen (Hendriks et al, 2007;Wilson et al, 2008) and bog ecosystems (Tuittila et al, 2000;Drösler, 2005).…”
mentioning
confidence: 88%
“…It has previously been shown that this layer releases large quantities of nutrients and dissolved organic carbon once waterlogged conditions have been re-established in peat (Zak and Gelbrecht, 2007). Furthermore, primary production and the deposition of plant litter in the top layer may increase CH 4 emissions under anoxic conditions (Tuittila et al, 2000;Juutinen et al, 2003;Wilson et al, 2008), as labile organic matter is a prerequisite for anaerobic CO 2 and CH 4 formation (Glatzel et al, 2004;Segers, 1998;Conrad, 1989). Raising the water table not only affects GHG exchange but also the vitality and composition of the vegetation (Drösler, personal communication;Clymo, 1984).…”
mentioning
confidence: 99%
“…There are, though, significant avoided costs. For instance, Wilson et al (2009) estimate that losses from drained industrial peatlands could be as much as 11 tonnes t CO 2 -eq per hectare per year, equal to a cost of €220 per hectare on the basis of global warming potential. On rewetting losses are reduced by around 9 tonnes CO 2 -eq.…”
Section: Carbon Industrial and Domestically Cut Bogsmentioning
confidence: 99%
“…Cutaway peatland restoration has been shown to reduce CO2 emissions [20], and even restore the carbon sequestration capacity compared to the original cutaway [21]. However, the return of anoxic conditions in the peatland results in an increase in CH4 flux, with 100 ha of restored wetlands emitting CH4 emissions of 105 tonnes of CO2-equivalents (CO2-eq) per year [22]. Restored peatlands are likely to contribute CH4 emissions of the same magnitude as natural peatlands [20].…”
Section: Restored Peatlandsmentioning
confidence: 99%
“…However, there can be considerable losses of soil carbon from the residual peat which continues to decompose [15,19]. In terms of CH4, afforested peatlands are likely to be a modest sink; however, considerable emissions are more likely from drainage ditches [22].…”
Section: Restored Peatlandsmentioning
confidence: 99%